Forest Regeneration Under Reduced- Impact and Conventional Logging in Lowland Mixed Dipterocarps Forest of East Kalimantan, Indonesia - Rusontoyo, Hari Priyadi (2003)
The lowland rain forests of the Bulungan Research Forest (now called as Malinau Research Forest) are important for their high species richness which constitutes a portion of the remaining frontier forest in Asia. Lowland dipterocarp forest is the most extensive forest type in the area. Trees may reach up to 35-40 m height. Dominant species with diameter are those of the Dipterocarpaceae family. The commercial timber species in the area is Shorea spp, Dipterocarpus spp, Hopea spp and Vatica spp. Agathis boomeensis is also another commercial species. It is the unique timber representative of the family Araucariaceae in the lowland and hill mixed dipterocarp forest of Borneo. Reduced-Impact Logging (RIL) trial has been carried out in the compartment of operational scale (over 100 ha). Twenty four permanents sample plots (PSPs), of one ha each have been randomly set up for a long term monitoring. All trees (dbh 20 cm) were measured and identified.The objective of study was to observe how far RIL can reduce logging damage as compared to conventional logging which was done in state-owned company, PT Inhutani II, East Kalimantan. Residual stand damage were calculated to be compared with initial density. In conventional logging, the damage which was created in diameter class of 20-50 cm dbh versus felling intensity were recorded as amounting 27% (in low logging intensity), 22% (medium), and 27% (high) from initial density. Meanwhile in diameter class above 50 cm dbh were 3.9% (low) and 6% (both medium and high). In contrast, in reduced-impact logging, residual stand damage in diameter class of 20-50 cm dbh were 10% (low), 20% (medium) and 29%(high). Meanwhile, in diameter class above 50 cm dbh were only 1 %(low), 3% (medium) and 6% (high). In line with those activities also to do monitoring PSPs, as well as to examine the stand structure and status of species composition of logged over forest under reduced impact and conventional logging. The study showed the overall density of saplings of approximately 4,600 stems/ha, which is mainly composed of two families, Euphorbiaceae and Dipterocarpaceae. Euphorbiaceae particularly dominated this storey. A total of 705 trees species were recorded from the permanent sample plots, of which 70 trees (9.29%) were dipterocarp species. Among the distributed dipterocarps species are Dipterocarpus lowii, D. stellatus, Shorea beccariana, S. brunescens, S. exelliptica, S. Macroptera, S. Maxwelliana, S. multiflora, S. parvifolia, S. rubra and S. venulosa. In this study, residual stand damage due to reduced impact and conventional logging with different logging intensity were also be demonstrated.